Modifying the platform-mediated avoidance task: A new protocol to study active avoidance within a social context in rats - Cassandra Kramer; Shannon Ruble; Troy D. Fort; Lexe West; Maria M. Diehl (PLoS ONE, 2025)
The platform-mediated active avoidance (PMA) task has been used to study the behavioral and neural mechanisms of a decision-based form of active avoidance. Across 10 days of PMA conditioning, rats learn to avoid a tone-signaled footshock by moving to a safe platform at the cost of forfeiting sucrose reward. Prior studies utilizing the PMA task involved rats learning to avoid alone in a solitary context, but we have recently modified the task to include a social context to determine how social cues may influence PMA acquisition. Additionally, we report novel measures of social interaction that occur during Social Partner PMA conditioning. This protocol provides a detailed methodology for studying active avoidance within solitary and social contexts, as well as key considerations when employing the PMA task.